A Comparative Review of Trenchless Cured-in-Place Pipe (CIPP) With Spray Applied Pipe Lining (SAPL) Renewal Methods for Pipelines - Hicks, John; Kaushal, Vinayak; Jamali, Koosha (Frontiers in Water, 2022)
Pipes have been used for thousands of years, the first record of copper piping dates to the Egyptians in 3000 BC. In today’s time, pipelines play a dramatic role in our everyday life and is a backbone of our society. Replacing and renewing our vast piping system is extremely important to maintain and grow the infrastructure around us. Trenchless methods (TM) can renew pre-existing piping, replace, and offer installation of new pipe(s). Two very common TMs are cured-in-place piping (CIPP) and spray-applied pipe lining (SAPL). These are great alternatives compared to open cut pipeline installation (OCPI) due to minimizing environmental impact and the total cost associated with renewing or replacing a pipe. Owners and engineers involved in a project which contain pipe renewal and or replacement should consider the time and social cost associated with each method. Cost alone should not be the one and only deciding factor. The objective of this review is to compare and contrast CIPP and SAPL pipeline renewal methods with references found over these renewal methods. This will be demonstrated with the use of a table that will consist of these parameters; environmental, mechanical properties, performance, cost, and methods. The method used for selecting specific articles/papers is intended to locate major factors that play a role in pipeline renewal using publications from the past years. Results show that reviewing, comparing, and understanding current research relating to pipeline renewal will allow for safer applications, increased efficiency, and pipeline longevity.